Time-of-day at symptom onset was not associated with infarct size and long-term prognosis in patients with ST-segment elevation myocardial infarction - Sager, Hendrik B.; Husser, Oliver; Steffens, Sabine; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Kastrati, Adnan; Ndrepepa, Gjin; Kessler, Thorsten (Journal of Translational Medicine, 2019)
Background: ST-segment elevation myocardial infarction (STEMI) displays circadian variability with the highest incidence in the morning hours. Data on whether the time-of-day at symptom onset affects infarct size or patients' long-term prognosis are conflicting. We sought to investigate the association of time-of-day at symptom onset with infarct size or long-term mortality in patients with STEMI undergoing primary percutaneous coronary intervention (PPCI). Methods: This study included 1206 STEMI patients undergoing PPCI. All patients underwent single photon emission computed tomography (SPECT) imaging with 99mTc-sestamibi before and 7-14 days after PPCI. The co-primary endpoints were final infarct size on day 10 after STEMI and all-cause mortality at 5-year follow-up. Time-of-day at symptom onset of STEMI was categorized in 6-h intervals. Results: In patients presenting from 0 to 6 h, 6 to 12 h, 12 to 18 h, and 18 to 24 h, the infarct sizes (median [25th-75th percentiles]) were 10.0 [3.0-24.7], 10.0 [3.0-24.0], 10.0 [3.0-22.0], and 9.0 [3.0-21.0] of the left ventricle, respectively (p = 0.87); the Kaplan-Meier estimates of 5-year all-cause mortality were 13.6%, 8.7%, 13.7% and 9.3%, respectively (log-rank test p = 0.30). After adjustment, time-of-day was not associated with infarct size (p ≥ 0.76 for comparisons with infarct size from reference [6-12 h] time interval) or 5-year all-cause mortality (p ≥ 0.25 for comparisons with mortality from reference [6-12 h] time interval). Time-of-day at symptom onset of STEMI was not associated with differences in the recovery of left ventricular ejection fraction 6 months after STEMI. Conclusions: In patients with STEMI undergoing PPCI, time-of-day at symptom onset was neither associated with scintigraphic infarct size, left ventricular ejection fraction recovery at 6 months nor with 5-year mortality.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Circadian rhythm; Infarct size; Primary percutaneous coronary intervention; ST-segment elevation myocardial infarction